Agreement between laboratory methods and the 4-compartment model in assessing fat mass in obese older Hispanic-American adults - Rogelio, Gonzalez-Arellanes; Urquidez Romero, Rene; Rodriguez-Tadeo, Alejandra; Julián, Esparza-Romero; Rosa Olivia, Méndez-Estrada; Erik, Ramírez-López; Alma-Elizabeth, Robles-Sardin; Bertha-Isabel, Pacheco-Moreno; Heliodoro, Alemán-Mateo (2021)
Background/objectives: Densitometry (Siri's and Bro zek's equations), hydrometry (by the deuterium dilution technique), and dual-energy X-ray absorptiometry (DXA) are three methods for estimating body composition. However, because they are all based on certain assumptions, they may not be applicable to aged and obese subjects due to changes in their body composition. Hence, the validity of these “laboratory methods” could be affected in obese older people. The main aim was to assess the agreement between densitometry, hydrometry, and DXA with the 4-compartment (4C) model to estimate fat mass (FM) in obese older Hispanic-American adults. As secondary goals, we explored whether the bias in densitometry and hydrometry results could be improved by modifying the assumptions regarding fatfree mass (FFM) density and hydration factor (HF) values, respectively. In the case of DXA, we explored the factors that contribute to bias. Subjects/methods: This is a cross-sectional study based on a sample of 171 obese subjects aged 60 years from 3 regions of northern Mexico. Body composition was assessed by the 4C model as the reference method and by all three laboratory methods. Agreement of the latter with the 4C model was probed by Bland and Altman analysis, a paired sample t-test, and simple linear regression analyses. In addition, the mean FFM density estimated in this sample, and HF values (published previously) of 0.737 and 0.753 for obese older Hispanic-American men and women, respectively, were considered as ethnic- and genderspecific values. These values were used to modify the densitometric and hydrometric equations in order to improve their bias. Finally, we tested whether the hydration status and indirect markers of adiposity are contributing factors to the bias of DXA using multiple linear regression analysis. Results: Siri's equation overestimated FM by 0.57 kg (p < 0.01), while Bro zek's equation, hydrometry, and DXA underestimated it by 1.24 kg, 0.89 kg, and 0.79 kg (p < 0.01), respectively, compared to the 4C model. The bias in the densitometry and hydrometry results was eliminated by substituting the ethnicand gender-specific values into the equations. Finally, we found that hip circumference contributes to the bias in DXA. Conclusion: The densitometry, hydrometry, and DXA methods are not interchangeable with the 4C model for assessing fat mass in obese, older Hispanic-American adults. The lack of agreement could indicate that the assumptions of each method do not apply to this population.